MYELOPEROXIDASE - A PROGNOSTIC MARKER IN CARDIO VASCULAR DISEASE - DEEPTI MANDSORWALE,; SURYAKANT NAGTILAK,; AARTI LALCHANDANI,; AJAI KUMAR SRIVASTAVA, (International Journal of Pharma and Bio Sciences, 2014)
Myeloperoxidase (MPO), a leukocyte derived enzyme linked to both inflammation and oxidative stress. Present study comprising 215 subjects [control (n=54), three patient subgroups (SAP=52, UAP=53 and AMI=56 respectively)] selected to evaluate systemic release of MPO, a characteristic feature in various referred sub-groups suffering from CVD correlated with levels of oxidative stress markers and traditional coronary disease risk factors in study subjects. Lipid profile, MDA, catalase and plasma MPO were analyzed by established techniques. Data suggests that CVD cases had significantly elevated levels of MDA, catalase and Lipid profile except HDL-C. Plasma MPO was found significantly elevated (p < 0.001) in UAP and AMI subgroups compared with control and SAP subgroup counterparts. Study concludes that plasma MPO levels play an important role in diagnosis of UAP & AMI subgroups and may be used as prognostic marker in evaluation of risk in patients with SAP.